2013
DOI: 10.1118/1.4795335
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of patient specific dosimetry in total body irradiation

Abstract: Actual dose measurement analysis of TBI patients revealed a potentially wide variance from the calculated dose. Based from their IVD method for TBI using Cobalt-60 irradiator and moving table, ± 10% over entire body is hard to achieve. However, it can be significantly improved with immediate feedback after the first fraction prior to subsequent treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…9,16 It is therefore encouraging that with the approach described in this study, it is possible to plan and deliver almost all doses within this range (Fig. 3).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…9,16 It is therefore encouraging that with the approach described in this study, it is possible to plan and deliver almost all doses within this range (Fig. 3).…”
Section: Discussionmentioning
confidence: 81%
“…Akino et al 16 suggested that corrections required for singlefraction treatments might be applied halfway through the treatment. However, the discrepancies reported for their moving- table Table 3 Comparison of measured and expected doses, for this study (also shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports, however, show that achieving these tolerances can prove challenging. Actual differences in administered dose have been observed to deviate greater than 35% from the prescription . As such, field homogeneity testing plays an important role in quality assurance testing of 60 Co irradiators.…”
Section: Introductionmentioning
confidence: 99%
“…A translational couch technique maintains a static beam and gantry, while the patient travels under the linac on a specialized translational couch 11. A homogeneous dose can be delivered by varying the speed of the couch movement 12, 13. Custom‐made lung shields and beam spoilers may still be required for these techniques.…”
Section: Introductionmentioning
confidence: 99%